Macrophages in microgravity: the impact of space on immune cells - Christopher Ludtka (Nature Portfolio, 2021)
Abstract The effects of a microgravity environment on the myriad types of immune cells present within the human body have been assessed both by bench-scale simulation and suborbital methods, as well as in true spaceflight. Macrophages have garnered increased research interest in this context in recent years. Their functionality in both immune response and tissue remodeling makes them a unique cell to investigate in regards to gravisensitive effects as well as parameters of interest that could impact astronaut health. Here, we review and summarize the literature investigating the effects of microgravity on macrophages and monocytes regarding the microgravity environment simulation/generation methods, cell sources, experiment durations, and parameters of interest utilized within the field. We discuss reported findings on the impacts of microgravity on macrophage/monocyte structure, adhesion and migration, proliferation, genetic expression, cytokine secretion, and reactive oxygen species production, as well as polarization. Based on this body of data, we make recommendations to the field for careful consideration of experimental design to complement existing reports, as the multitude of disparate study methods previously published can make drawing direct comparisons difficult. However, the breadth of different testing methodologies can also lend itself to attempting to identify the most robust and consistent responses to microgravity across various testing conditions.